Outcomes of Moderately Preterm Infants of Insulin-Dependent Diabetic Mothers - Gray, Keyaria D.; Saha, Shampa; Battarbee, Ashley N.; Cotten, Charles Michael; Boghossian, Nansi S.; Walsh, Michele C.; Greenberg, Rachel G.; for the Eunice Kennedy Shriver National Institute of Child Health Human Development Neonatal Research Network (American Journal of Perinatology, 2022)
Objective Little is known about the hospital outcomes of moderately preterm (MPT; 29 0/7–33 6/7 weeks gestational age) infants born to insulin-dependent diabetic mothers (IDDMs). We evaluated characteristics and outcomes of MPT infants born to IDDMs compared with those without IDDM (non-IDDM).Study Design Cohort study of infants from 18 centers included in the MPT infant database from 2012 to 2013. We compared characteristics and outcomes of infants born to IDDMs and non-IDDMs.Results Of 7,036 infants, 527 (7.5%) were born to IDDMs. Infants of IDDMs were larger at birth, more often received continuous positive pressure ventilation in the delivery room, and had higher risk of patent ductus arteriosus (adjusted relative risk or aRR: 1.49, 95% confidence interval [CI]: 1.20–1.85) and continued hospitalization at 40 weeks postmenstrual age (aRR: 1.55, 95% CI: 1.18–2.05).Conclusion MPT infants of IDDM received more respiratory support and prolonged hospitalizations, providing further evidence of the important neonatal health consequences of maternal diabetes.Key Points
Keywords: moderate preterm; infants; diabetes; insulin